A combined sensorimotor skill and strength training program improves postural steadiness in rhythmic sports athletes - Tsaklis, P.; Karlsson, J. E.; Grooten, W. J.; Äng, B. O. (Human Movement, 2008)
Purpose. The aim of this controlled trial was to evaluate the effects of a combined sensorimotor skill and strength training program on postural steadiness in junior females performing rhythmic sports gymnastics. Basic procedures. Twenty-six rhythmic sports athletes, aged 9 to 12 years, were randomized into one of two groups; a 6-week experimental group or to a control group, (during the 2004-2005 training period). In the experimental group, a sensorimotor and back-muscle-strengthening regime was added to the everyday training, while the control group continued with their ordinary training. Before and after the intervention, and at a 12-month follow, bipedal-stance center of foot pressure (CoP) sway area was examined with a statokinesigram indicating amplitude of vertical pressure fluctuations after stimulation of the vestibular system, and the distribution of body weight between legs. Main findings. At the 6- week follow-up, the experimental group had a larger decrement in CoP sway area (-59%, p = 0.004) and in asymmetrical body weight distribution (-58%, p < 0.001) compared to the control group (-0.1% and 2.3%, respectively), but not at the 12-month followup. Conclusions. The present sensorimotor skill and strength training program indicated short-term improved postural steadiness in rhythmic sports athletes. Exercises that specifically emphasize somatosensory and back strength aspects of training for postural steadiness may advantageously be integrated into their training routines.